Are Asian Dragons and Tigers Catching Up? - Noguera-Santaella, J (Springer Verlag, 2019)
This paper studies the catching up process in per capita income of the so-called Asian Dragons and Tigers. It contributes to the literature in several ways. First, it tests the catching up hypothesis using the longest time span ever considered, from 1870 to 2014. Second, it documents the experiences of these two groups of countries and provides potential explanations for them. Third, the analysis of the paper uses the Kejriwal and Perron (J Time Ser Anal 31:305–328, 2010) algorithm which allows us to endogenously estimate multiple structural breaks in the level and the trend of the series without prior knowledge of their integration level. This surpasses technical concerns of previous empirical studies. Fourth, it inquiries into how the Asian financial crisis affected the catching up process among the Dragons and Tigers economies. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.